1998
DOI: 10.1007/bf02467448
|View full text |Cite
|
Sign up to set email alerts
|

Direct resolution of a new antifungal agent, voriconazole (UK-109,496) and its potential impurities, by use of coupled achiral-chiral high-performance liquid chromatography

Abstract: Key WordsColumn liquid chromatography Enantiomer separation Voriconazole (UK-109,496) Effect of organic mobile-phase modifier SummaryCoupled achiral-chiral high-performance liquid chromatography (HPLC) with an achiral amino-based column coupled with a chiral amylose-based column has been used for qualitative and quantitative determination of the potential chiral and achiral impurities of Voriconazole (UK-109,496), a new antifungal agent with two stereogenic centres. The effect of the organic mobile-phase modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The serial coupling strategy was also successfully exploited by Angelo et al [12] for the quantitative LC determination of the methadone enantiomers and of some of its related cyclic N-demethylated metabolites. Analogously, Ferretti et al [13] reported on the simultaneous chemo-and enantioseparation for the identification and determination of the antifungal agent Voriconazole, its stereoisomers and potential impurities by LC. Bicker et al [14] treated the problem of limited diastereoselectivity, i. e. insufficient chemoselectivity for diastereomeric forms of pyrethroic acids by a serial chiral -chiral in-line coupling of two distinct quinine carbamate-based anionexchangers one of which delivered the diastereoselectivity increment which was missing on the other column that however showed better enantioselectivity.…”
Section: Introductionmentioning
confidence: 96%
“…The serial coupling strategy was also successfully exploited by Angelo et al [12] for the quantitative LC determination of the methadone enantiomers and of some of its related cyclic N-demethylated metabolites. Analogously, Ferretti et al [13] reported on the simultaneous chemo-and enantioseparation for the identification and determination of the antifungal agent Voriconazole, its stereoisomers and potential impurities by LC. Bicker et al [14] treated the problem of limited diastereoselectivity, i. e. insufficient chemoselectivity for diastereomeric forms of pyrethroic acids by a serial chiral -chiral in-line coupling of two distinct quinine carbamate-based anionexchangers one of which delivered the diastereoselectivity increment which was missing on the other column that however showed better enantioselectivity.…”
Section: Introductionmentioning
confidence: 96%
“…One potential solution to overcome this limitation is to use multidimensional liquid chromatography (2D-LC) approaches, where the two dimensions are often based on different separation mechanisms [10][11][12]. Much more rarely, tandem column systems consisting of columns connected in series showed promising results with a significantly improved overall separation performance [13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…Since 1990, high-performance liquid chromatography (HPLC) with ultraviolet, fluorescence, or electrochemical detection has been used extensively for the determination of antifungal drugs in biological samples (e.g., ketoconazole [7,8], clotrimazole [9], itraconazole [10][11][12][13], fluconazole [14][15][16][17], and voriconazole [18,19]), although other analytical methods including bioassays and gas chromatography using electron-capture or nitrogen-selective detection have also been described. On the other hand, the use of capillary electrophoresis (CE) continues to grow rapidly as an alternative and complementary analytical technique to HPLC for the separation of small organic molecules such as pharmaceutical agents and drug metabolites.…”
Section: Introductionmentioning
confidence: 99%